2009
DOI: 10.1038/tpj.2009.52
|View full text |Cite
|
Sign up to set email alerts
|

Upregulating CD59: a new strategy for protection of neurons from complement-mediated degeneration

Abstract: An increasing number of studies have shown a critical role for the membrane attack complex, synthesized on activation of the terminal pathway of the complement system, in causing demyelination and neuronal death in neurodegeneration. The aim of this study was to develop a strategy to increase the resistance of neurons to complement damage by modulating the expression of membrane complement regulatory protein CD59, the only inhibitor of the terminal pathway of the complement cascade. We exploited our recent fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The ongoing debate of whether the complement system is 'friend or foe' in ischemic brain injury [60] may be explained by the complexity of the system and the manifold pathways which are activated by the complement system, and the different ways complement may be inhibited at different levels of the complement cascade. Thus, our data which demonstrates model- and gender-specific effects of MAC-inhibition by CD59a, replenishes the current understanding of the complement system in ischemic brain injury and thus may contribute to the development of future therapeutical strategies [61]. …”
Section: Discussionmentioning
confidence: 89%
“…The ongoing debate of whether the complement system is 'friend or foe' in ischemic brain injury [60] may be explained by the complexity of the system and the manifold pathways which are activated by the complement system, and the different ways complement may be inhibited at different levels of the complement cascade. Thus, our data which demonstrates model- and gender-specific effects of MAC-inhibition by CD59a, replenishes the current understanding of the complement system in ischemic brain injury and thus may contribute to the development of future therapeutical strategies [61]. …”
Section: Discussionmentioning
confidence: 89%
“…These regulators contribute to control the innate immune response in the CNS. Some of NIRegs could be potential therapeutical molecules [62,105-108]. Griffith et al found that accumulation of human factor H in the brain parenchyma protected neurons from complement opsonization, axonal injury, and leukocyte infiltration [109].…”
Section: Roles Of Complement Activation In Alzheimer’s Diseasementioning
confidence: 99%
“…On the other hand, however, CRP binds to apoptotic cells, protects the cells from assembly of the terminal complement components, i.e. form membrane attack complex to which neurons are very vulnerable (Kolev et al 2010), and sustains an anti-inflammatory innate immune response (Gershov et al 2000). CRP, however, is only moderately expressed in the brain.…”
Section: Smoking Inflammation and Adhdmentioning
confidence: 99%